Sindh Employer's Survey 2010 - World Bank (Washington, DC, 2014)
Although some progress has been made in the basic education sector in Pakistan, currently, less than 1 percent of the population aged 10 years and above is trained in occupational skills. This situation could be improved through an identification of employment opportunities, a provision of appropriate training, promotion of effective employment policy from the government, and a stronger linkage between those who are trained and a labor market. In order to identify what, when and where training and skills are needed and how skills are imparted, this paper analyses the results of the employer survey conducted in November 2009 towards 1,000 selected enterprises. The results of the survey will provide various benchmarks which can be used over time to: measure how Sindh Technical Education and Vocational Training Authority (STEVTA) and Benazir Bhutto Shaheed Youth Development Program (BBSYDP) can improve existing program outcomes, and to monitor changes in labor market demand so that STEVTA and BBSYDP can shift resources appropriately. Authors conclude this paper with eight findings and recommendations: 1) rising demand for skills indicates the need for skills program, 2) need for training of specific skills such as on-the-job training and communication skills, 3) need for specific trainings for occupations demanded, 4) improved employment prospects, 5) trainees' need for direct contacts to firms and preparation for interviews, 6) need for an increase in visibility of BBSYDP, 7) need for a reform in public institutions, and 8) current focus of firm's internal trainings on educated and skilled employees.